Kegiatan Semarak Ramadhan Siswa Kristen SMA Negeri 2 Sipora Dengan Baca Gali Alkitab - Herlince Rumahorbo; Hasahatan Hutahaean; Sindar Siregar; Megawati Siagian (Journal Of Human And Education (JAHE), 2023)
Semarak Ramadhan activity is an annual agenda of Senior High Schools in West Sumatra Province. They receive spiritual guidance according to their religion. At SMA Negeri 2 Sipora, one of the activities for Christian students is Bible Reading and Digging (BGA) training. Teachers see that students need to obtain material on a simple Bible study model for personal devotion. As one writes, the Bible is not easy to understand and find its message. However, the Bible Reading method is believed to be a solution for the Christian community, including high school students. The implementation of this training was carried out on 195 Protestant Christian students by delivering the steps of the BGA method and practicing. For the example of extracting nats, selected from books with the narrative genre. Students were divided into 10 groups practicing using methods on different Bible passages. After group work, satisfactory results were seen. Each group was able to finded the message of God's Word correctly using the BGA method. Three questions in the extracting and finding stages of the news in the BGA method can be answered correctly by trainees. This activity hopes that students will be diligent and diligent in reading and meditating on God's Word for fresh, strong, and swift spiritual growth every day.